Il rhombos e la trottola (Mantichora. Italian Journal of Performance Studies, 2020)
Both of Greek origin, the Italian words “rombo” and “trottola” are linked by at least two other aspects that define their symbolic function: their coexistence in the Orphic myth of Dionysus’ dismemberment by the Titans and their functional and semantic similarities in contemporary folklore. In particular, this essay emphasises that the Sicilian term for rhombus - lapuni (“hornet”) - is the same used to designate the spinning top (trottola) that, turning perfectly on its axis at maximum speed, almost disappears from the view. We, then, explore the multiple meanings related to the games made with the spinning top and to the parts that compose this object, and the use of the rhombus in initiatory rituals. The characteristics of the latter, in spite of the temporal and spatial distance of the societies that express them (from the Bororo to the Greeks, from the Sicilians to the Australian Aborigines), turn out to be very close to each other. This allows us to reflect on the existence of “elementary ideas” and “cultural universals”.